Prevalence and Ethnic Variability of G6PD Deficiency Among Newborns in the Northern Emirates: A Three-Year Retrospective Study at Thumbay Hospitals, Ajman, UAE - H. Alfeel, Ayman; A. Osman, Hussam; Y. E. Yousif, Tagwa; Algarni , Abdulrahman; Saboor, Muhammad; O. Hussein, Salah E. (Journal of Neonatal Surgery, 2025)
SUMMARY BACKGROUND Glucose-6-phosphate dehydrogenase (G6PD) deficiency is one of the most common enzymatic inherited red cell disorder. This study investigated the prevalence and distribution of G6PD deficiency among newborns in Thumbay hospital and other health care facilities across the Northern Emirates in United Arab Emirates (UAE). Methods This was a retrospective cross-sectional study focusing on data of newborns screened for G6PD levels over three years (2020–2022) at Thumbay Laboratory, Ajman. Resutls New-borns from Southern Asia exhibited the highest prevalence of G6PD deficiency, with 88 cases (40.3%) out of 3,921 newborns. Western Asia also showed significant prevalence with 75 cases (34.4%) among 729 new-borns. Conversely, regions like Eastern Asia and Europe/America reported negligible or no cases. Conclusion The findings of this study indicate a high prevalence of G6PD deficiency in newborns born in the Northern Emirate of the UAE, particularly those from Southern and Western Asia, with Southern Asia showing the highest rate. Males had lower G6PD levels as compared to females, though these differences were not statistically significant